A GRANDE VEDETE DO FUTURO? A cultura empreendedora no Instituto Federal de Mato Grosso do Sul - Ariela Castelani Bertoli (2023)
This work aims to understand the social construction of an entrepreneurial culture within the campus of the Federal Institute of Education, Science and Technology of Mato Grosso do Sul, in Campo Grande. The theoretical framework is based, in particular, on the considerations of Luc Boltanski and Ève Chiapello about what they call the “new spirit of capitalism”. The ethnographic research, carried out in the school routine of a public institution, served as a reference for understanding, through institutional documents, pedagogical projects of courses, pedagogical practices and speeches from teachers and students, the construction of an entrepreneurial culture. The Weberian methodological instrumental, around the notion of “ideal type”, is used here to understand the observed social actions, in order to reflect on how a new ideal of economic conduct has been presented to the agents - the students - who attend the school environment. Through the results found here, it was possible to verify that the construction of an entrepreneurial culture within the school takes place in a scenario of conflicts and contradictions and is permeated by an ambiguity of senses, sometimes referring to work and sometimes, especially, to values that guide all other spheres of social life.